Preparing for International Classification of Diseases, 10th Revision, Clinical Modification Implementation. Issue 1 (January 2015) - Dexheimer, Judith W.; Scheid, Beth; Babaoff, Arash; Martens, Saundra; Kennebeck, Stephanie; Harper, Marvin B.; Hoffman, Jeffrey M.; Zorc, Joseph J.
<x xml:space="preserve">Abstract</x> Abstract The International Classification of Diseases, 10th Revision, is required to be used by the Centers for Medicare and Medicaid Services health care billing data starting in October 2015 in the United States. The International Classification of Diseases, 10th Revision, is an update to the International Classification of Diseases, Ninth Revision, and contains approximately 70, 000 codes compared with 14, 000 codes. We aimed to discuss how our institution is updating the coding system in a manner that alleviates the possible burden placed on providers including more coding information required and longer load times. We performed a simulation test including testing the diagnosis calculator, timing, and how well the new and old codes mapped. We conducted a gap analysis to ensure that coding could begin in October of 2015 with minimal service interruptions. We will describe strategies and procedures to transition between systems while maintaining efficiency and helping to improve classification.